On *-representations of algebras given by graphs - Ivanov, S. V. (Methods of Functional Analysis and Topology, 2007)
*-algebras given by trees generated by projections with Temperley-Lieb type relations are considered in this work. Formulas of representations are built by algorithms for *-algebras, associated with the Dynkin diagrams, and we get estimates for the parameters at which non-trivial *-representations of the *-algebras exist.